![y = (x^{2} - 5x + 5)\cdot e^{x - 5}\\ y' = (2x - 5)e^{x - 5}\ + \ e^{x-5}\cdot(x^{2} - 5x + 5)\\ y = (x^{2} - 5x + 5)\cdot e^{x - 5}\\ y' = (2x - 5)e^{x - 5}\ + \ e^{x-5}\cdot(x^{2} - 5x + 5)\\](https://tex.z-dn.net/?f=y+%3D+%28x%5E%7B2%7D+-+5x+%2B+5%29%5Ccdot+e%5E%7Bx+-+5%7D%5C%5C+y%27+%3D+%282x+-+5%29e%5E%7Bx+-+5%7D%5C+%2B+%5C+e%5E%7Bx-5%7D%5Ccdot%28x%5E%7B2%7D+-+5x+%2B+5%29%5C%5C)
Найдем стационарные точки.
\begin{cases} e^{x - 5} = 0}\\ 2x-5+x^{2} - 5x + 5 = 0 \end{cases}\\ \begin{cases} --\\ x^{2} - 3x = 0 \end{cases}\\ x(x - 3) = 0 <=> \begin{cases} x_{min} = 0\\ x_{max} = 3 \end{cases}\\ " alt="(2x - 5)e^{x - 5}\ + \ e^{x-5}\cdot(x^{2} - 5x + 5) = 0\\ e^{x-5}\cdot (2x-5+x^{2} - 5x + 5) = 0\\ <=> \begin{cases} e^{x - 5} = 0}\\ 2x-5+x^{2} - 5x + 5 = 0 \end{cases}\\ \begin{cases} --\\ x^{2} - 3x = 0 \end{cases}\\ x(x - 3) = 0 <=> \begin{cases} x_{min} = 0\\ x_{max} = 3 \end{cases}\\ " align="absmiddle" class="latex-formula">
Т.к. нам нужно минимальное значение функции найдем: ![y(x_{min}) y(x_{min})](https://tex.z-dn.net/?f=y%28x_%7Bmin%7D%29)
![y_{min} = 5\cdot e^{- 5} = \frac{5}{e^{5}} y_{min} = 5\cdot e^{- 5} = \frac{5}{e^{5}}](https://tex.z-dn.net/?f=y_%7Bmin%7D+%3D+5%5Ccdot+e%5E%7B-+5%7D+%3D+%5Cfrac%7B5%7D%7Be%5E%7B5%7D%7D)